Analysis Of Quality Of Service (Qos) For Xl's 4g Lte Network In Padang Panjang City - Taufik Hidayat; Zurnawita Zurnawita; Popy Maria (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of telecommunications necessitates continuous improvement in service quality, including 4G LTE networks. Padang Panjang's mountainous geography presents specific challenges, requiring a Quality of Service (QoS) analysis to evaluate public service levels. This study aims to measure and analyze the QoS of XL's 4G LTE network in Padang Panjang based on latency, jitter, packet loss, and throughput.The research employed an experimental method, conducting drive tests on planned routes. Data was collected using a smartphone with the TEMS Pocket application to measure parameters and Wireshark to analyze packet data. Results were processed using TEMS Discovery to assess performance against QoS standards.Findings showed an average throughput of 6.46 Kbps, latency of 0.000358 ms, jitter of 0.000356 ms, and packet loss of 0.3%. According to the TIPHON QoS standard, latency, jitter, and packet loss fall into the excellent category. However, throughput is classified as very poor. This indicates that while the XL 4G LTE network in Padang Panjang is stable and capable of supporting real-time services like VoIP and video conferencing, its data transfer speed performance remains severely inadequate. The study concludes that significant improvement in throughput is needed to meet overall service quality expectations.